Hydrogen Sulfide: A Signal Molecule in Plant Cross-Adaptation - Li, Zhong-Guang; Min, Xiong; Zhou, Zhi-Hao (Frontiers in Plant Science, 2016)
For a long time, hydrogen sulfide (H2S) has been considered as merely a toxic byproduct of cell metabolism, but nowadays is emerging as a novel gaseous signal molecule, which participates in seed germination, plant growth and development, as well as the acquisition of stress tolerance including cross-adaptation in plants. Cross-adaptation, widely existing in nature, is the phenomenon in which plants expose to a moderate stress can induce the resistance to other stresses. The mechanism of cross-adaptation is involved in a complex signal network consisting of many second messengers such as Ca2+, abscisic acid (ABA), hydrogen peroxide (H2O2) and nitric oxide (NO), as well as their crosstalk. The cross-adaptation signaling is commonly triggered by moderate environmental stress or exogenous application of signal molecules or their donors, which in turn induces cross-adaptation by enhancing antioxidant system activity, accumulating osmolytes, synthesizing heat shock proteins (HSPs), as well as maintaining ion and nutrient balance. In this review, based on the current knowledge on H2S and cross-adaptation in plant biology, H2S homeostasis in plant cells under normal growth conditions; H2S signaling triggered by abiotic stress; and H2S-induced cross-adaptation to heavy metal, salt, drought, cold, heat and flooding stress were summarized, and concluded that H2S might be a candidate signal molecule in plant cross-adaptation. In addition, future research direction also has been proposed.